TREND 25 TAHUN (1988-2012) PENELITIAN TUGAS AKHIR MAHASISWA PENDIDIKAN BIOLOGI FKIP UNIVERSITAS RIAU - Firdaus LN; Raja Hussien Arief (Biogenesis, 2014)
A desciptive Studies on thesis of biology education student has been explored at Faculty of Teacher Training and Education, University of Riau. Data are based on the student Thesis published at the last twenty-five years (1988-2012). As much as 525 Thesis abstract has been analyzed by using total sampling technique. The subject area, research methodes, biology concept and biology teaching concept were indentified. Data were analyzed descriptively. The results shows that most of the thesis focus on Senior High School as a subject of their research. Descriptive and survey methodes are the most chosen by the students in their thesis. At least 57 biology concepts has been Studied as independent variables, and the concept of pollution is the most frequent. There are 40 biology concepts has been Studied as dependent variables, and the most frequent on plant vegetative growth. We found at least 152 biology inctructional concepts has been Studied as independent variables. Biological subject content is the most ferequent. There are 20 biology instructional concepts has been Studied as dependent variables, and the most frequent is learning achievement concept.Keywords: biological education research, biology undergraduate student, Biological concept, biology instructional concept, research in science education, research methology